Tinjauan Perbandingan Metode Fabrikasi Dan Aplikasi Komposit Matricks Logam: Wawasan Dari Literatur Terkini - Fitriyah, Hamidah; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2026)
Metal Matrix Composites (MMCs) have become a major focus in materials research due to their ability to combine the superior properties of metals and non-metallic reinforcements. This review article focuses on a comparative analysis of two key literatures, "Recent Advances in Fabrication of Metal Matrix Composites: A Systematic Review" and "Metal Matrix Composites," which represent perspectives on fabrication technique innovation and fundamental understanding of material properties. A literature search conducted through Scopus and Google Scholar using the keywords "metal matrix composites," "fabrication techniques," and "material applications" for the period 2015–2025 yielded relevant articles as supporting literature. The analysis shows that key advances in the past decade include the development of powder metallurgy, stir casting, and additive manufacturing methods, which have significantly impacted the mechanical strength, wear resistance, and thermal stability of MMCs. Meanwhile, the fundamental literature provides a strong theoretical foundation for selecting matrices and reinforcements for specific applications. The results of this review confirm that integrating knowledge from these two main areas, enriched with supporting literature, can accelerate innovation and optimization of MMC applications across various industrial sectors.